KAJIAN RISIKO LONGSOR DALAM UPAYA MITIGASI BENCANA DI KOTA PADANG PANJANG PROVINSI SUMATERA BARAT - farhan, Anesan (JURNAL BUANA, 2026)
Abstract Landslides are natural disasters that occur in mountainous or hilly areas, especially during the rainy season, Padang Panjang City has high rainfall, areas with slopes > 40% or in hilly areas that have the potential for landslides. The background of this research is to study the level of landslide disaster risk in Padang Panjang City and analyze landslide disaster mitigation efforts. The method used is a mixed method and uses overlay analysis techniques to analyze landslide disaster risk studies while mitigation efforts use AHP analysis techniques. The results of the research are the level of landslide danger in the medium class with an area of ​​1417.02 ha or 69%, the low class with an area of ​​632.06 ha, and the high class with an area of ​​7.97 ha, the level of disaster vulnerability in the medium and low classes. The risk level for landslides in the medium class is 1305.18 ha or 63%, for the low class it is 669.38 ha or 33%, and the high classification is 82.49 ha or 4%. The main priority in mitigation efforts is the availability of landslide disaster risk information and maps. Keywords: Hazard, vulnerability, risk assessment, AHP, mitigation